Nuclear Magnetic Resonance of Water in Cold Acclimating Red Osier Dogwood Stem - Burke, Michael J. (1974)
The pulsed and continuous-wave nuclear magnetic resonance of water in cold-acclimating red osier dogwood (Cornus stolonifera Michx) stem showed reduced relaxation times and increased line width. The reduction of relaxation times suggests an over-all restriction in the motional characteristics of the water. The increased line width is not related to a molecular property of the water, but is useful in estimating the initiation of cold acclimation. Biphasic relaxation characteristics may be related to partitioning of the water at the cellular level. The liquid water content of the stem was a weak function of temperature between −25 and −55 C, corresponding to approximately 0.15 gram of water per gram of dry stem. The quantity of unfrozen water at subfreezing temperatures was not strongly dependent on the degree of cold acclimation. It is concluded that the ability of dogwood to survive low temperatures depends on its ability to tolerate diminished quantities of liquid water.